2012
DOI: 10.1111/j.1651-2227.2012.02629.x
|View full text |Cite
|
Sign up to set email alerts
|

Single course of antenatal steroids did not alter cortisol in preterm infants up to 18 months

Abstract: Aims To determine whether a single course of antenatal dexamethasone alters resting cortisol at 3, 8 and 18 months corrected age in preterm infants. Methods Preterm infants born ≤32 weeks gestational age were recruited during 2001–2004 from a single neonatal intensive care unit. Resting salivary cortisol was collected at least once at 3, 8 and 18 months corrected age in a longitudinal cohort. A mixed-effects repeated measures analysis was used to accommodate cases with less than complete follow-up. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Reports are indicating that the effect on adrenal function may be transient in nature [29]. In addition, the influence of prenatal steroids on resting salivary cortisol levels at the age of three months (corrected age) has recently been investigated without finding any association [30].…”
Section: Discussionmentioning
confidence: 99%
“…Reports are indicating that the effect on adrenal function may be transient in nature [29]. In addition, the influence of prenatal steroids on resting salivary cortisol levels at the age of three months (corrected age) has recently been investigated without finding any association [30].…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids are indispensable for early development and essential for many peripheral and neuronal maturation processes (McEwen, 1987). Importantly, even if a single course of antenatal steroid is considered safe and does not alter HPA axis function (Dalziel et al, 2005;Gover et al, 2011), repeated doses of synthetic antenatal steroids have been associated with restricted growth and altered cardiovascular, HPA and metabolic function (for review see: Sloboda et al, 2005). An increase in endogenous glucocorticoids, as seen after prenatal stress, can lead to earlier earflap and eye opening and faster righting in rat pups (Secoli and Teixeira, 1998), which suggests that increased glucocorticoids levels accelerate maturation of the fetus beyond lung maturation.…”
Section: Early Life Maternal Conditions Change Adult Phenotype: Lessomentioning
confidence: 99%
“…(13) Early exposure to inflammatory signals leading to activation of the HPA axis may result in reprogramming of this stress axis, causing long-term functional changes. Possible mechanisms for altered programming in these circumstances include exposure to excess endogenous glucocorticoids(14) or direct action of cytokines on the brain during critical windows of brain development; however, higher cortisol levels were not driven by either antenatal(15) or postnatal(7) glucocorticoid exposure in our previous cohort . Several animal studies have shown a long term effect of early infection on the HPA axis.…”
Section: Introductionmentioning
confidence: 54%